Review of offshore energy in Malaysia and floating spar platform for sustainable exploration - Islam, A.B.M.; Jameel, Mohammed; Jumaat, Mohd Zamin; Shirazi, S.M.; Salman, Firas A. (Elsevier, 2012)
Rapidly rising trends of fuel consumption indicate enormous energy crisis of global proportions in near future. Following the trend, Malaysia's fuel consumption has been increasing by an annual rate of 7.2 since 1990 and has even reached 44.9 Mtoe in 2008. It is forecasted to reach 207.3 Mtoe by the year 2030. Due to serious depletion of reserves in various onshore locations, the exploration process is expanded to offshore deeper waters. Seven sedimentary basins belonging to Malaysia, in South China Sea, show great promise to be excellent sources of hydrocarbons. For deep-sea exploration fixed offshore structures are not feasible. An economical alternative is Spar platforms, which are floating structures ideal for exploration of deep water deposits. In this research, Malaysian experience in offshore hydrocarbon exploration is investigated. Various kinds of operational Spar platforms are censoriously explored and their recent technical developments are reviewed. The study reveals that Malaysia's primary energy requirements were met (in year 2008) with natural gas by 43.4 of the total, crude oil by 38.2, coal by 15.3 and hydropower by 3.1; indicating evidently that natural gas and crude oil are still the predominant energy sources. Out of the total energy, around 70 oil and 85 natural gas come from offshore fields. These large figures highlight the necessity to consider economically viable alternatives. Spar platform is an innovative marine structure designed to conduct such deep sea explorations. First commissioned Spar at Kikeh field of Malaysia is testimony to immense potential and possibilities of incorporating Spar platforms in the country's deep reserves for sustainable energy generation. Classic Spar, Truss Spar, Cell Spar and Cell-truss Spar are identified to be well suited for these environments. Since the offshore fields are located at waters with more than 1000 m depth, Spar platforms can be successfully installed at these Malaysian deep water fields. (c) 2012 Elsevier Ltd. All rights reserved.